Associations of Immune Cell Subsets With Coronary Artery Calcium Incidence and Progression in the Multi‐Ethnic Study of Atherosclerosis - Patel, Riddhi D.; Buzkova, Petra; Huber, Sally; Landay, Alan; Budoff, Matthew; Bis, Joshua C.; Olson, Nels; Rich, Stephen; Heckbert, Susan R.; Manichaikul, Ani; Floyd, James; Tracy, Russell P.; et al. (Journal of the American Heart Association, 2025)
Limited data exist on associations of immune cell subsets with longitudinal changes in subclinical coronary artery disease. In the MESA (Multi-Ethnic Study of Atherosclerosis) study, we used a case-cohort approach to explore associations of 28 immune cell subsets measured at baseline (2000-2002) with longitudinal changes in coronary artery calcium (CAC). We examined incident CAC from examination 2 (2002-2004) through examination 5 (2010-2012) in participants with 0 CAC at baseline using multivariable-adjusted Cox regression. In participants with CAC >0 at baseline, we analyzed changes in CAC through examination 5 using multivariable-adjusted linear mixed models. Because no studies have investigated immune cells and longitudinal CAC changes, analyses were considered exploratory, with <0.05 as the threshold for possible significance. Of 975 participants with immune cells subsets and CAC measurements at baseline, 378 had CAC 0 at baseline (mean age, 58.4; 37.0% men) and 597 had CAC >0 at baseline (mean age, 65.7; 57.6% men). Natural killer cells were associated with higher incident CAC (hazard ratio [HR], 1.26 per SD higher natural killer cell proportion; =0.03), whereas T helper type cells were associated with lower incident CAC (HR, 0.81; =0.04). B cells were associated with CAC progression (β=53.1 Agatston units per SD higher B-cell proportion, =0.04), whereas CD14+CD16+ monocytes (β=-71.6; =0.03) and T regulatory cells (β=-61.9; =0.03) were associated with lower CAC progression. Natural killer cells may be associated with incident CAC and T regulatory cells may be associated with attenuated CAC progression, among other findings. These warrant replication and experimental investigation.